African Swine Fever in Saxony—Disease Dynamics - Katja Schulz; Sandra Blome; Michael Richter; Tessa Carrau; Christoph Staubach; Carola Sauter-Louis (Viruses)
African swine fever (ASF) emerged in Germany in 2020. A few weeks after the initial occurrence, infected wild boar were detected in Saxony. In this study, data from wild boar surveillance in Saxony were analyzed. The analysis focused on the eastern districts of the state, where the disease likely spread through infected wild boar. Additionally, data from Meissen, located approximately 65 km further west, were examined. In Meissen, the disease emerged one year later, and a human-mediated introduction was suspected. To evaluate the progression of ASF in the two study areas over time, data from active and passive surveillance were analyzed both descriptively and using a Bayesian space–time model. Prevalence estimates were calculated for wild boar testing positive for the ASF virus and for ASF-specific antibodies. Higher prevalence estimates were observed in the eastern districts, indicating a stronger viral load, consistent with patterns seen in other European regions. Over time, seroprevalence increased, suggesting an accumulation of surviving wild boar. The findings provide important insights into the epidemiology of ASF in wild boar over time. They complement the existing knowledge and support targeted ASF control measures. This is particularly significant, as ASF continues to spread across Europe rather than being successfully eradicated.